Abusive Supervision and Job Dissatisfaction: The Moderating Effects of Feedback Avoidance and Critical Thinking - Qian, Jing; Song, Baihe; Wang, Bin (Frontiers in Psychology, 2017)
Although research on the antecedents of job dissatisfaction has been developed greatly, we know little about the role of abusive supervision in generating job dissatisfaction. The contingencies under which abusive supervision relates to employees’ job dissatisfaction are still unknown. The present study aimed to fill this research gap by empirically exploring the abusive supervision-job dissatisfaction relationship as well as examining the moderating roles of feedback avoidance and critical thinking on this relationship. We tested the hypotheses with data from a sample of 248 employees from a high-tech communications company in northern China and found that: (a) abusive supervision was positively related to job dissatisfaction; (b) the positive relationship was moderated by both employees’ feedback avoidance and critical thinking. We conclude by extracting the theoretical as well as practical contributions, along with a discussion of the promising directions for future research.